2020
DOI: 10.48550/arxiv.2009.11673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uniqueness for an inverse coefficient problem for a one-dimensional time-fractional diffusion equation with non-zero boundary conditions

Abstract: We consider initial boundary value problems for one-dimensional diffusion equation with time-fractional derivative of order α ∈ (0, 1) which are subject to non-zero Neumann boundary conditions. We prove the uniqueness for an inverse coefficient problem of determining a spatially varying potential and the order of the time-fractional derivative by Dirichlet data at one end point of the spatial interval. The imposed Neumann conditions are required to be within the correct Sobolev space of order α. Our proof is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Now we study the direct problem (1.1), especially the solution representation. One distinct feature of problem (1.1) is that it involves an inhomogeneous Neumann boundary condition, which has not been extensively studied in the literature ( [34,23] for relevant works). Following [34], we exploit the one-dimensional nature of problem (1.1), and derive a series representation of the solution u.…”
Section: Well-posedness Of the Direct Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…Now we study the direct problem (1.1), especially the solution representation. One distinct feature of problem (1.1) is that it involves an inhomogeneous Neumann boundary condition, which has not been extensively studied in the literature ( [34,23] for relevant works). Following [34], we exploit the one-dimensional nature of problem (1.1), and derive a series representation of the solution u.…”
Section: Well-posedness Of the Direct Problemmentioning
confidence: 99%
“…One distinct feature of problem (1.1) is that it involves an inhomogeneous Neumann boundary condition, which has not been extensively studied in the literature ( [34,23] for relevant works). Following [34], we exploit the one-dimensional nature of problem (1.1), and derive a series representation of the solution u. The derivation is based on the standard separation of variable technique (see, e.g., [35] and [14,Section 6.2]).…”
Section: Well-posedness Of the Direct Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The recovery of the space-dependent potential q in the classical diffusion equation from lateral Cauchy data has been extensively discussed, and several uniqueness results have been obtained [31,34,41]. The study on related inverse problems for time-fractional models is of more recent origin, starting from [7] (see [19] for an early tutorial) and there are a few works on recovering a spatially dependent potential from lateral Cauchy data [22,36,37,44]. Rundell and Yamamoto [36] showed that the lateral Cauchy data can uniquely determine the spectral data when u 0 ≡ f ≡ 0, and proved the uniqueness of the potential q by the classical Gel'fand-Levitan theory.…”
Section: Introductionmentioning
confidence: 99%